The Witness Must Speak the Truth - Siniša Franjić (Law and Economy, 2024)
At the beginning of the testimony, the witness will be warned that he is obliged to tell everything he knows about the case, as well as that giving a false testimony is a criminal act. A witness may be asked to promise to tell the truth. After that, he or she will be asked for personal information and the relationship with the defendant and the injured party. He will be invited to present everything he knows about the subject, and then he will be asked questions for verification, completion and clarification. He or she will always be asked how he or she knows what he or she is testifying about. If the witness stated facts that he no longer remembers during the previous examination or if he or she deviates from his testimony, he or she will be presented with the previous testimony and will be asked why he is testifying differently now.